2011
DOI: 10.1074/jbc.m111.250175
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Right Open Reading Frame 2 (Rio2) Protein Kinase by Polo-like Kinase 1 Regulates Mitotic Progression

Abstract: Background: Rio2 is a protein kinase and involved in ribosomal subunit maturation. Results: Rio2 is a novel substrate of Plk1. Overexpression of Rio2 causes a prolonged mitotic exit whereas knockdown of Rio2 accelerates mitotic progression. Conclusion: Plk1-dependent phosphorylation of Rio2 regulates the timing of the metaphase-anaphase transition. Significance: We unveiled the novel role of Rio2 and its phosphorylation by Plk1 in regulating mitotic progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…RIOK2 has several putative and mapped phosphorylation sites, including at least one putative Akt phosphorylation site (www.phosphosite.org, Figure S8). Other studies show that RIOK2 phosphorylation can be stimulated by EGFR, and can be carried out by Polo-like kinase 1 [21], [61], and perhaps these events contribute to Akt-mediated regulation of RIO kinase levels. Of note, though standard GBM cells lacking PTEN showed high levels of RIO kinase expression, non-transformed astrocytes lacking PTEN did not show high levels of endogenous RIO kinase protein expression relative to astrocytes with intact PTEN.…”
Section: Discussionmentioning
confidence: 95%
“…RIOK2 has several putative and mapped phosphorylation sites, including at least one putative Akt phosphorylation site (www.phosphosite.org, Figure S8). Other studies show that RIOK2 phosphorylation can be stimulated by EGFR, and can be carried out by Polo-like kinase 1 [21], [61], and perhaps these events contribute to Akt-mediated regulation of RIO kinase levels. Of note, though standard GBM cells lacking PTEN showed high levels of RIO kinase expression, non-transformed astrocytes lacking PTEN did not show high levels of endogenous RIO kinase protein expression relative to astrocytes with intact PTEN.…”
Section: Discussionmentioning
confidence: 95%
“…Knockdown of RIOK1 arrests yeast cells at S and mitosis phases 7 . RIOK2 acts as the substrate of PLK1 and is required for the proper mitotic progression in Hela cells 8 . In addition, our recent work has found that down‐regulation of RIOK3 causes G1 arrest, whereas overexpression of RIOK3 accelerates cell cycle progression in glioma cells 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To determine which region of Plk1 is required for its interaction with P-TEFb, pCMV FLAG-Plk1(1-330) and pCMV FLAG-Plk1(330-603) were generated as described previously [23] (Figure 2A) and transfected into 293T cells. The data from immunoprecipitation demonstrated that the C-terminal polo-box domains of Plk1 are mainly responsible for its binding with P-TEFb complex, while its N-terminal region shows very weak interaction with P-TEFb.…”
Section: Resultsmentioning
confidence: 99%
“…pCMV FLAG-Plk1 and its mutants and bacteria expression plasmids pET-30a-Plk1, pET-30a-Plk1 TD (constitutively active form of Plk1) and pET-30a-Plk1 KD (kinase deficient form of Plk1) were generated as described previously [23]. pCMV myc-Plk1 were made by cloning Plk1 cDNA into the pCMV myc vector (BD Clontech) at EcoRI-XhoI sites.…”
Section: Methodsmentioning
confidence: 99%